Enhancing Critical Reflective Practice in Science Education Through a STEAM Approach - Thapaliya, Pratima (Journal of Transformative Praxis, 2023)
This article aimed to explore teachers’ beliefs on reflective practice in their professional life and envision perspectives for transforming their practice. I used auto/ethnography as a research methodology for critically reflecting on the self and others’ lived experiences of teaching science, mathematics, and technology in the context of Nepal. I explored that reflective practice is required for understanding and transforming our deep-seated dominant cultural practices. On becoming a critically reflective practitioners, we can incorporate a trans-disciplinary STEAM approach while designing and implementing a curriculum, pedagogy, and assessment system that helps understand learners’ sociocultural backgrounds, beliefs, values, assumptions, and feelings for authentic, inclusive, and meaningful learning.